The Syndrome of Inherited Partial SBP2 Deficiency in Humans - Dumitrescu, Alexandra M. (Mary Ann Liebert, Inc., 2010)
Selenium (Se) is an essential trace element required for the biosynthesis of selenoproteins. Selenocysteine insertion sequence (SECIS) binding protein 2 (SBP2) represents a key trans-acting factor for the co-translational insertion of selenocysteine into selenoproteins. In 2005, we reported the first mutations in the SBP2 gene in two families in which the probands presented with transient growth retardation associated with abnormal thyroid function tests. Intracellular metabolism of thyroid hormone (TH) and availability of the active hormone, triiodothyronine, is regulated by three selenoprotein iodothyronine deiodinases (Ds). While acquired changes in D activities are common, inherited defects in humans were not known. Affected children were either homozygous or compound heterozygous for SBP2 mutations. Other selenoproteins, glutathione peroxidase, and selenoprotein P were also reduced in affected subjects. Since our initial report, another family manifesting a similar phenotype was found to harbor a novel SBP2 mutation. In vivo studies of these subjects have explored the effects of Se and TH supplementation. In vitro experiments have provided new insights into the effect of SBP2 mutations. In this review we discuss the clinical presentation of SBP2 mutations, their effect on protein function, consequence for selenoproteins, and the clinical course of subjects with SBP2 defects. Antioxid. Redox Signal. 12, 905–920.